The relationship between age, technology acceptance model and grades obtained in the training of professional emergency services - Lluch, David; Gros, Begoña (Proceedings of the International Conference on Networked Learning, 2018)
This contribution reports on findings from a study on firefighters’ grades obtained in technology-supported training courses in Catalonia. The role of firefighters has changed dramatically over the past few years and will continue to do so as modernization progresses. This will have implications for everything associated with the service and in particular in relation to the type and delivery of basic training. The wider role of rescue work and the demands of community fire prevention require skills that need to be taught in a different manner. A review of current research concerning distance learning (Holmgren, 2015) and the use of digital technologies shows that there are few studies on firefighter training. This paper aims to describe and analyse the relationships between the firefighters’ age, the intention to use technology to learn and the grades obtained obtained in online training courses. To explain the influence of digital literacy on individuals’ intention to pursue online learning, we integrate the concept of digital literacy with the Unified Theory of Acceptance and Use of Technology (measured using the TAM2 questionnaire). Technology-supported distance learning is an increasingly common mode in practical professional training courses. In line with this development, campus-based firefighter training in Catalonia is implemented using a distance mode and blended courses. Data has been analysed from two courses carried out in a Moodle environment, one of which was delivered in a blended learning mode for aspiring firefighters and another was presented in e-learning mode for active firefighters with different levels of experience. The total number of participants was 247. The results obtained when analysing the variables of age, grade obtained and TAM2 scores show that there is no significant relationship between them. However, we have found a relationship in the case of the intention to use technology for learning and the grade obtained in the course. The results suggest that the acceptance and, therefore, the use of technology does not depend on the student’s age. We have found a positive relationship in the case of students on the Basic Training Course for Firefighters in the Intention to Use (IU), Perceived Usefulness (PU) and Voluntariness (V) scales referring to the grades they obtained.